2016
DOI: 10.1177/0363546516654687
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Changing the Joint Kinematics of Knees With a Ruptured Anterior Cruciate Ligament on the Molecular Biological Responses and Spontaneous Healing in a Rat Model

Abstract: Elucidating the relationship between the mechanotransduction mechanism and healing responses in knees with completely ruptured ACLs may result in the development of novel nonsurgical treatment that enables the ACL to spontaneously heal in patients who are not suitable for reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…A recent study established a relationship between the spontaneous healing response and abnormal tibiofemoral subluxation by designing an ACL spontaneous healing rodent model. In this model, abnormal tibiofemoral subluxation following surgically transected ACL was prevented by using nylon structures at the extra-articular capsule (Figures 2 and 3) [41]. The authors demonstrated spontaneous healing of the ACL in this model, and observed that the gap between the tibial and femoral remnants of the ligament was bridged by tissue that consisted of important extra-cellular matrix components including collagen type I and III.…”
Section: Novel Candidate For Acl Healingmentioning
confidence: 85%
See 1 more Smart Citation
“…A recent study established a relationship between the spontaneous healing response and abnormal tibiofemoral subluxation by designing an ACL spontaneous healing rodent model. In this model, abnormal tibiofemoral subluxation following surgically transected ACL was prevented by using nylon structures at the extra-articular capsule (Figures 2 and 3) [41]. The authors demonstrated spontaneous healing of the ACL in this model, and observed that the gap between the tibial and femoral remnants of the ligament was bridged by tissue that consisted of important extra-cellular matrix components including collagen type I and III.…”
Section: Novel Candidate For Acl Healingmentioning
confidence: 85%
“…A better understanding of the reasons for the failure of ACL to spontaneously heal will help us develop newer treatment methods. Although we are still unaware of the entire mechanism, and the signaling pathways involved in ACL spontaneous healing, recent studies have identified few probable candidates that may be possible key players [41,[47][48][49][50]. Some studies have reported that injured ACL has the same functional healing response as other extra-articular ligaments in terms of cellularity and vascularity.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research showed that changing the joint kinematics of a knee with complete ruptured ACL results in the down-regulation of inflammatory responses [ 33 ] and leads to spontaneous healing [ 27 ]. These previous studies used the CAM model used for the purpose of controlling abnormal knee joint movement without restricted knee flexion (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the skin was closed only in the ACL-T group. In the CAM group, a 2–0 nylon suture (Prolene, Ethicon Endo-Surgery Japan) was passed through the tibial bone tunnel posterior to the condyle of the distal end of the femur and was then tied to the joint in order to prevent abnormal tibial translation, according to the same procedure as that used in previous study [ 27 ]. The nylon suture provided a directed traction force to resist the anterior motion of the tibia without restricted knee flexion (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation